ISLAH SEBAGAI DALIH: STUDI KASUS ‘PENYELESAIAN KONFLIK’ PERISTIWA TANJUNG PRIOK (1984) DAN TALANG SARI (1989) PASCA REZIM ORDE BARU - Akmaliah, Wahyudi (P2KK LIPI, 2014)
Abstract A term of islah is quite familiar for Indonesian Muslims. It is an Islamic reconciliation term adopted from Al-Quran and Sunnah to end a conflict. With this term, those people who have been conflicting try to improve their relation to look for a better future by getting rid of their anger and vengeance. The cases of Tanjung Priok (1984) and Talang Sari (1989) tragedy, which caused hundreds of killed Muslims during Soeharto regime, are real examples to see how islah is practiced. Instead of being the best way for conflict resolution, it was part of the problems causing those cases unfinished in the formal court. It had caused the group of the victims divided within two groups; pros and cons of islah. Using islah as the pretext, many of the victims tended to finish it informally with the violators, although the rest still insisted to bring it to the court. The fragmented memory among them about the cases caused a lot of difficulties to prove it legally. Exploring the Islam sources as well as the case of Tanjung Priok and Talang Sari in Post-New Order Regime, this paper examines whether islah is a solution or precisely a part of the problem. This paper aims to put the term of islah and its significant in a proper way; therefore, this paper can contribute to the development of peace and conflict studies. Keywords: Islah, Tanjung Priok (1984), Talang Sari (1989), islamic law, victims, conflict resolution